Inovasi Pangan Lokal Berbasis Pisang: Strategi Pemberdayaan Masyarakat Pemenang Lombok Utara menuju Produk Berdaya Saing - Diah Miftahul Aini; Gladeva Yugi Antari; Sri Laela Isnaeni; Jumadil Jumadil; Firman Abadi Saputra (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Banana is an abundant commodity in Lombok, and its processing into value-added products requires community empowerment strategies to ensure the production of high-quality products.This community service activity aims to empower the community in Pemenang, North Lombok, by developing banana-based processed product innovations, especially banana chips, to improve the welfare and competitiveness of local products. The problems faced by the community include the low added value of banana agricultural products, non-standard processing techniques, and limited understanding of food safety, packaging, and certifications such as halal and Good Manufacturing Practice (GMP). This activity was carried out through technical training on banana chip processing, attractive packaging design, and the socialization of food safety standards and certification processes. The results showed increased production skills, awareness of the importance of legality and food safety, and community readiness to develop a competitive local processed-based business. This activity is the first step to building community economic independence based on local potential integrated with industry standards.